Islam and education / Nasiruddin Mizy - Mizy, Nasiruddin (2015)
Islam is not simply a religion as like as other religions of the world, but it is a complete, comprehensive, pragmatic and scientific religion. All aspect of life is the subject matter of this religion. But the foundation stone of this is laid on education, because the very commencement of this religion is with an imperative instruction to attain education. The very first verse of this religion is 'Iqra'(read). The subsequent verses are also comprises of the prime element of education...'Qalam'(pen). And then Allah defined education that ''taught man that he knew not' i.e. knowing the unknowing is education. The very inception of Adam was with education. He was taught by Allah and they were not. So the criterion of his superiority over angels was the knowledge and education. Educating the disciples was the prime duty of the last Messenger of Allah and all other prophet and messengers. All these things manifest the importance of education. But whenever we discuss education relating to Islam, curve out in the mind of the people a scenario of various disciplines of religious thoughts and notions, keeping aloof from the disciplines of knowledge close to the daily life of human being. The main purpose of this paper is to explore the real scenario of Islamic education. The paper will be comprised of the ideological and philosophical basis of Muslim education and the actual cause of the dichotomy of Muslim educational thoughts. Also the paper will portray the effacing process of the dichotomy and the scenario of the integration between so called Deeni and Duniyawi system education. It is very important to mention the role of Muslim intellectuals in this concern. Besides, rulers of powerful Muslim countries and institutions also have a vital concern about exploring the real scenario of Islamic education.